2022
DOI: 10.3390/v14020384
|View full text |Cite
|
Sign up to set email alerts
|

Phage-Displayed Mimotopes of SARS-CoV-2 Spike Protein Targeted to Authentic and Alternative Cellular Receptors

Abstract: The evolution of the SARS-CoV-2 virus during the COVID-19 pandemic was accompanied by the emergence of new heavily mutated viral variants with increased infectivity and/or resistance to detection by the human immune system. To respond to the urgent need for advanced methods and materials to empower a better understanding of the mechanisms of virus’s adaptation to human host cells and to the immuno-resistant human population, we suggested using recombinant filamentous bacteriophages, displaying on their surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 119 publications
(164 reference statements)
1
9
0
Order By: Relevance
“…Frontiers in Microbiology 06 frontiersin.org pathogen invasions in this lab (Zhao et al, 2012) or others (Hall et al, 2009;Wei et al, 2020). This study and several other efforts (Anand et al, 2021;Sokullu et al, 2021;Ballmann et al, 2022;Labriola et al, 2022;Petrenko et al, 2022;Sevenich et al, 2022;Yang et al, 2022) demonstrated that PhD was a plausible method for generating possible therapeutics to treat COVID-19 as well. For example, Petrenko used phage-displayed spike S1 protein mimotopes to search for "all" cellular receptors, including authentic and alternative ones.…”
Section: Synthetic C2 and C6 Peptides Blocked The Binding Of Spike-tr...supporting
confidence: 59%
See 2 more Smart Citations
“…Frontiers in Microbiology 06 frontiersin.org pathogen invasions in this lab (Zhao et al, 2012) or others (Hall et al, 2009;Wei et al, 2020). This study and several other efforts (Anand et al, 2021;Sokullu et al, 2021;Ballmann et al, 2022;Labriola et al, 2022;Petrenko et al, 2022;Sevenich et al, 2022;Yang et al, 2022) demonstrated that PhD was a plausible method for generating possible therapeutics to treat COVID-19 as well. For example, Petrenko used phage-displayed spike S1 protein mimotopes to search for "all" cellular receptors, including authentic and alternative ones.…”
Section: Synthetic C2 and C6 Peptides Blocked The Binding Of Spike-tr...supporting
confidence: 59%
“…For example, Petrenko used phage-displayed spike S1 protein mimotopes to search for “all” cellular receptors, including authentic and alternative ones. Interestingly, FGFR3 was identified as an alternative receptor to S proteins ( Petrenko et al, 2022 ). Since FGFR3 manifested a distribution pattern different from that of ACE2, Petrenko’s work expanded the area of SARS-CoV-2 targets and might lead to the discovery of novel pathogenesis of SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Petrenko et al described a model termed “phage mimicry” to display the viral receptor-binding site on the spike protein by phage display and by employing recombinant filamentous bacteriophages. They used the model to investigate the binding mechanism of the virus to the corresponding receptor in vitro [ 11 ]. Further, Yang et al used phage display technology to research the specific binding of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the SARS-CoV-2 spike S1, the protein’s phage mimotopes which resemble the shape of the viral receptor-binding (RB) sites, were created. Utilizing recombinant bacteriophages with surface mimotopes may provide a molecular probe for analyzing viral infectivity and could be effective in COVID-19 vaccine development [ 59 ]. Another study used mycobacteriophages to show SARS-CoV-2 RB motif segments.…”
Section: Bacteriophages: a Tool For The Expression And Presentation O...mentioning
confidence: 99%